PENYULUHAN PROTOKOL KESEHATAN PENCEGAHAN DAN PENGENDALIAN COVID-19 DI PANTI ASUHAN BAITUL ARIEF KOTA BANDUNG - Ida Lisni; Entris Sutrisno; Dewi Mardiyah; Suherdin Suherdin; Desi Trisiani (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
The virus that causes COVID-19 is mainly transmitted through the droplets that are produced when an infected person coughs, sneezes, or exhales. We can be infected when we breathe the air containing the virus, we are too close to people who are already infected with COVID-19. Therefore, it is necessary to conduct outreach to the public regarding health protocols to prevent and control the transmission of covid-19. The Baitul Arief Orphanage, which is located in the middle of the city and a densely populated area, has 85 foster children who have activities both from foster children and activities from guests and donors who come and go. To prevent foster children from contracting COVID-19 by changing their lifestyle in accordance with government regulations, it is necessary to conduct Health Protocol Covid-19 Prevention and Control Counseling. The methods of implementing these activities include location surveys, presenting initiatives, implementing Covid-19 Health Protocol counseling, handing over hand washing equipment from the UBK community service team, 6-step hand washing practice with soap for, ordering the covid task force at an orphanage, and evaluation. Activities are documented and published through social media and mass media and journals. The results of education and evaluation of written tests increase children's knowledge and understanding as prevention and control of Covid-19. The lowest average score for foster children with elementary education level and the highest score for foster children with tertiary education. The existence of the Covid-19 Task Force in the form of an orphanage contributes to changes in behavior and builds self-awareness for foster children at the Baitul Arief orphanage in Bandung City.